Plant-Based Probiotic Beverages in Preventing the Growth of Foodborne Pathogenic Bacteria: A Review - Wulansari, Nadya Treesna (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Foodborne illnesses are mostly caused by bacteria. Bacteria, including Escherichia coli, Salmonella sp., Shigella sp. and Staphylococcus aureus, are the most common causes of foodborne diseases. One alternative to reduce the risk of infection from bacteria that cause foodborne diseases is the consumption of probiotic beverages, which has become a natural alternative in improving digestive health and endurance. One type of probiotic drink that is gaining increasing attention is plant-based kombucha tea. Plant parts that can be used as kombucha tea are fruits, leaves, and flowers and have antibacterial activity with various categories of inhibition zone strength. This research uses a systematic review and collects relevant articles, with 14 articles as the main reference. The analysis found that salak Bali fruit, pineapple honey fruit, belimbing wuluh fruit, tea leaves, soursop leaves, telang flowers, gardenia flowers, and red seaweed have the potential as a probiotic kombucha tea drink that can inhibit the growth of pathogenic bacteria that cause foodborne diseases. The categories of inhibition zones produced ranged from weak to very strong, with inhibition zone diameters ranging from 4.20 mm to 24.7 mm. The optimal zone of inhibition of this probiotic drink is influenced by the plant parts used, the length of fermentation, the type of substrate, the test method and the type of bacteria. Plant-based probiotic beverages show effective antibacterial activity against foodborne pathogens and offer valuable insights into microbial interactions and sustainable food biotechnology in scientific learning.